Controlling shareholder share pledging and Enterprise Cost Stickiness: Evidence from Chinese Firms - Li Ziyang; Zhang Yingyue; Tan Xiaohan; Yu Wen (E3S Web of Conferences, 2020)
Using a sample of Chinese enterprises pledge during the period 2008-2017, this paper investigates the cost management behavior of enterprises during the pledge period of major shareholders’ stock rights. Our findings show that with the increase of the equity pledge rate, the cost stickiness of enterprises is enhanced. Further analysis shows that the behavior that the controlling shareholder invests the equity pledge funds to a third party weakens the cost stickiness of the enterprise. We further contribute to the literature on sticky cost and equity pledge by discussing the strategic choices of major shareholders to avoid risks during the equity pledge period.